Paper Soap Daun Belimbing Wuluh Sebagai Skin Moisturizer: Paper Soap Starfruit Leaves As A Skin Moisturizer - Talitha Cahyaningrum; Ayu Putri Brilian Subhan; Eka Nur Rahmawati; Dwi Teju Nurita Mami Zulfa; Fadila Aulia Zulfa; Agitya Resti Erwiyani (Universitas Ngudi Waluyo, 2024)
Star fruit leaves are compounds that have potential as antibacterial and moisturize the skin. Star fruit leaves can be formulated into various pharmaceutical dosage forms so that added value is obtained, one of which is paper soap. Paper soap contains the active substance of star fruit leaf ethanol extract combined with avocado oil as a moisturizer. This study aims to make a paper soap formulation from star fruit leaf extract and avocado oil. Paper soap is made in F1, F2 and F3 formulas containing star fruit leaf extract with concentrations of 5%, 10% and 15% respectively. The observed parameters of paper soap preparations include organoleptis, pH, foam stability, antibacterial, irritation of rabbit eyes and skin moisture. The formula of star fruit leaf extract paper soap contains secondary metabolites of flavonoids, saponins and tannins. Paper soap parameter test results meet requirements on organoleptis, pH, foam stability, antibacterial and irritation of the rabbit's eyes. The formula of star fruit leaf extract paper soap can increase skin moisture in all formulas. ABSTRAK Daun belimbing wuluh merupakan senyawa yang memiliki potensi sebagai antibakteri dan melembapkan kulit. Daun belimbing wuluh dapat diformulasikan menjadi berbagai bentuk sediaan farmasi sehingga diperoleh nilai tambah salah satunya paper soap. Paper soap memiliki kandungan zat aktif ekstrak etanol daun belimbing wuluh dikombinasikan dengan avocado oil sebagai moisturizer. Penelitian ini bertujuan untuk membuat formulasi paper soap dari ekstrak daun belimbing wuluh dan avocado oil. Paper soap dibuat dalam formula F1, F2 dan F3 yang mengandung ekstrak daun belimbing wuluh berturut-turut dengan konsentrasi sebesar 5%, 10% dan 15%. Parameter yang diamati dari sediaan paper soap meliputi organoleptis, pH, stabilitas busa, antibakteri, iritasi pada mata kelinci dan kelembapan kulit. Formula paper soap ekstrak daun belimbing wuluh mengandung metabolit sekunder flavonoid, saponin dan tannin. Hasil uji parameter paper soap memenuhi persyaratan pada organoleptis, pH, stabilitas busa, antibakteri dan iritasi pada mata kelinci. Formula paper soap ekstrak daun belimbing wuluh dapat meningkatkan kelembapan kulit pada semua formula.